Music benefits on postoperative distress and pain in pediatric day care surgery - Valeria Calcaterra; Selene Ostuni; Irene Bonomelli; Simonetta Mencherini; Marco Brunero; Elisa Zambaiti; Savina Mannarino; Daniela Larizza; Riccardo Albertini; Carmine Tinelli; Gloria Pelizzo (MDPI AG, 2014)
Postoperative effect of music listening has not been established in pediatric age. Response on postoperative distress and pain in pediatric day care surgery has been evaluated. Forty-two children were enrolled. Patients were randomly assigned to the music-group (music intervention during awakening period) or the non-music group (standard postoperative care). Slow and fast classical music and pauses were recorded and played via ambient speakers. Heart rate, blood pressure, oxygen saturation, glucose and cortisol levels, faces pain scale and Face, Legs, Activity, Cry, Consolability (FLACC) Pain Scale were considered as indicators of response to stress and pain experience. Music during awakening induced lower increase of systolic and diastolic blood pressure levels. The non-music group showed progressive increasing values of glycemia; in music-group the curve of glycemia presented a plateau pattern (P<0.001). Positive impact on reactions to pain was noted using the FLACC scale. Music improves cardiovascular parameters, stress-induced hyperglycemia. Amelioration on pain perception is more evident in older children. Positive effects seems to be achieved by the alternation of fast, slow rhythms and pauses even in pediatric age.